posted by Fatima on .
a particle is projected vertically upward with the velocity u m/s and after t(s) another particle is projected upwards from the same point and with the same initial velocity. proof that the particle will meet after a lapes of (u/g + t/2)seconds from the instance of the first particle.
Using t for time, and s for the delay,
ut - (g/2)t^2 = u(t-s) - (g/2)(t-s)^2
ut - (g/2)t^2 = ut - us + gst - (g/2)t^2 - (g/2)s^2
-(g/2)s^2 - us + gst = 0
gst = us + (g/2)s^2
t = u/g + s/2
reverting to the t notation originally used, ta-da!
thank u very much steve...am grateful